Design and Implementation of a DC Motor Control Platform Using the LabVIEW Programming Environment and the Microcontroller - نويره, ابراهيم; ثائر أحمد إبراهيم , (Latakia University Journal -Engineering Sciences Series, 2024)
The research deals with the design and implementation of a DC motor control platform intended for educational purposes using the Arduino microcontroller and the LabVIEW software environment. The designed system monitors the working status of the DC motor, measures its parameters (intensity of the current drawn - rotational speed - torque - load ratio) and draws its speed-torque curve, as well as an emergency stop when the nominal values of the current are exceeded. The results of testing the designed system on a parallel induction DC motor with a power of 24W showed that the designed system performs its functions correctly and achieves its desired purpose in terms of: The possibility of monitoring the values of the parameters of the tested motor in real time and the extent of changes in the values of these parameters when the load on the motor axis increases, as the value of the intensity of the current drawn increases, as well as the value of the torque, while the value of the rotational speed decreases. Controlling the start and stop of the motor and activating the emergency state when the nominal current value of the tested motor (2A) is exceeded in order to protect against overload. Plot the speed-torque curve of the tested motor at different load levels.